Synthesis of 8-Hydroxyquinoline-functionalized polyglycidy methacrylate resin and its efficient adsorption and desorption for Pb(II). Issue 39 (20th August 2016) - Liu, Chunping; Sun, Xiaoli; Liu, Lin; Liu, Junshen; Qi, Minyi; An, He
Abstract: The adsorbent 8-hydroxyquinoline-modified PGMA (HQPGMA resin) was synthesized via "graft from" method. The adsorption and desorption performances for Pb(II) were investigated in detail. The maximum uptake was determined at 1.38 mmol g −1 with an initial concentration of Pb(II) 0.02264 mol L −1, pH 5.81, and temperature 25°C. The equilibrium time of adsorption kinetics for Pb(II) was 600 min. The adsorption process conformed to pseudo-second-order model. Film diffusion was the rate-limit step. Freundlich model fits the adsorption isothermal process. The thermodynamic parameters implied the adsorption was exothermic and spontaneous. Pb(II) adsorbed on the resin can be eluted by a range of concentrations of hydrochloric acid from 0.2 to 0.8 mol L −1 solution. The optimal concentration of hydrochloric acid solution was achieved with 0.4 mol L −1, which resulted in a desorption rate of 92.38%. The resin demonstrated reusability with same effect after three times of adsorption/desorption cycles.